2014
DOI: 10.1187/cbe.13-05-0093
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effectiveness of an Educational Card Game as Supplementary Material in Understanding Selected Topics in Biology

Abstract: To help students understand and apply basic biological concepts in a challenging and interactive format, this study focused on the development, effectiveness, and evaluation of an educational card game. The test supported that the use of this educational card game is more effective than the traditional method. The students perceived that the material is “very satisfactory.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 15 publications
5
39
0
5
Order By: Relevance
“…Their responses and interpretations revealed that the use of educational games in the teaching process helps students to learn and improve certain skills, as well as increase their academic success and knowledge retention. The students listed the benefits of educational games:  They make the lesson more entertaining  They promote collaboration among students  They encourage active student participation  They increase motivation towards the lesson  They make lessons enjoyable and attract attention to the topic  They encourage effective communication among students  They facilitate learning and provide visual learning  They enable students to express themselves  They help students to reinforce their knowledge by reviewing the topics  They keep students engaged in the material  They empower students to correct their own mistakes  They enable to overcome challenges  They boost students' self-confidence Similar to those found in this study, many studies in the related literature on using games to teach various topics [2,3,4,5,7,8,15,17,18,19,20,21,22,23,24,32,35,37,38] report that teaching with games enhances students' motivation as well as increases their motivation, promotes active participation in lessons and the development of positive attitudes, and makes lessons more entertaining and pleasant.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Their responses and interpretations revealed that the use of educational games in the teaching process helps students to learn and improve certain skills, as well as increase their academic success and knowledge retention. The students listed the benefits of educational games:  They make the lesson more entertaining  They promote collaboration among students  They encourage active student participation  They increase motivation towards the lesson  They make lessons enjoyable and attract attention to the topic  They encourage effective communication among students  They facilitate learning and provide visual learning  They enable students to express themselves  They help students to reinforce their knowledge by reviewing the topics  They keep students engaged in the material  They empower students to correct their own mistakes  They enable to overcome challenges  They boost students' self-confidence Similar to those found in this study, many studies in the related literature on using games to teach various topics [2,3,4,5,7,8,15,17,18,19,20,21,22,23,24,32,35,37,38] report that teaching with games enhances students' motivation as well as increases their motivation, promotes active participation in lessons and the development of positive attitudes, and makes lessons more entertaining and pleasant.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
“…Biology students often have difficulty grasping biological concepts. For example, many students need to memorize complex words to understand the topic, which distracts them from the lesson [17]. For this reason, methods to ensure students' motivation and participation should be incorporated into the teaching process.…”
Section: Introductionmentioning
confidence: 99%
“…The observed effect size is comparable with results from RCTs of high school interventions using researcher-developed tests (mean effect size = 0.34; Lipsey et al. , 2012 ) and small-scale RCTs of short-term college biology curricular supplements (e.g., Cohen's d = 0.56; Gutierrez, 2014 ).…”
Section: Resultssupporting
confidence: 71%
“…[19] Most reports detail the creation of card or board games, and at least one reports the results of using an interactive video game. [20][21][22] Figure 4: Real time analysis of data entered by students. The chart reflects the results of simulations carried out by students using the computer simulator to identify the optimal level of vaccination against measles in order to protect unvaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%